2018
DOI: 10.1016/j.phro.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mass density variations on an electron Monte Carlo algorithm for radiotherapy dose calculations

Abstract: Background and Purpose: A key step in electron Monte Carlo dose calculation requires converting Computed Tomography (CT) numbers from a tomographic acquisition to a mass density. This study investigates the dosimetric consequences of perturbations applied to a calibration table between CT number and mass density. Materials and Methods: A literature search was performed to define lower and upper bounds for physically reasonable perturbations to a reference CT number to mass density calibration table. Electron b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Due to the non-bijective nature of this relationship, the exact composition of the tissue surrogate phantom will bias the accuracy of subsequent HU to electron density conversions in human tissues with lower energy CT (kVCT) being more sensitive to exact elemental composition than higher energy CT [3]. As an example of this, uncertainties in mass density [4] have been found to produce significant changes (of up to 12.5%) to the Monte Carlo calculated dose distribution for physically reasonable perturbations of the CT to density conversion tables.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the non-bijective nature of this relationship, the exact composition of the tissue surrogate phantom will bias the accuracy of subsequent HU to electron density conversions in human tissues with lower energy CT (kVCT) being more sensitive to exact elemental composition than higher energy CT [3]. As an example of this, uncertainties in mass density [4] have been found to produce significant changes (of up to 12.5%) to the Monte Carlo calculated dose distribution for physically reasonable perturbations of the CT to density conversion tables.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of variations of these parameters on dose calculation in inhomogeneous and homogeneous media has been studied and found significant [14]. Fang et al [15] have evaluated the effect of mass density variations on dose calculations by electron Monte Carlo algorithm and found that the electron transport is strongly dependent on the voxel medium and inhomogeneity must be dealt in with care.…”
Section: Figurementioning
confidence: 99%
“…Nevertheless, research in the field of CT imaging is still ongoing to improve image quality and reduce artefacts for more accurate dose calculation by using e.g. novel reconstruction algorithms [21] , [22] , [23] , [24] , [25] . With the clinical availability of proton therapy, the requirements for CT-based density estimation changed enormously as stopping power determination and dose calculation depend strongly on the tissue composition [26] , [27] .…”
Section: Ct Imaging For Rtmentioning
confidence: 99%